2009
DOI: 10.1097/inf.0b013e318199f61b
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of Routinely Used Childhood Vaccines When Coadministered With the 10-Valent Pneumococcal Non-typeable Haemophilus influenzae Protein D Conjugate Vaccine (PHiD-CV)

Abstract: Coadministration of PHiD-CV with commonly used childhood vaccines induced high levels of seroprotection/seropositivity against all targeted diseases. No evidence of negative interference on the immune response to any of the coadministered vaccine antigens was observed when compared with the current routine practice of 7vCRM coadministration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
44
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(54 citation statements)
references
References 29 publications
9
44
0
1
Order By: Relevance
“…Antibody concentrations against the diphtheria and tetanus antigens were higher when PHiD-CV was co-administered, presumably due to the diphtheria toxoid and tetanus toxoid carrier proteins used for serotypes 19F and 18C, respectively, in PHiD-CV. 35 This was shown in previous studies to result in an enhanced anti-PRP response when a tetanus-conjugate Hib vaccine was co-administered with PHiD-CV. 35 In our study, we also observed a trend for a higher anti-PRP antibody GMC in the PHiD-CV group compared to the HAV control group, although this difference did not reach statistical significance.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 88%
See 1 more Smart Citation
“…Antibody concentrations against the diphtheria and tetanus antigens were higher when PHiD-CV was co-administered, presumably due to the diphtheria toxoid and tetanus toxoid carrier proteins used for serotypes 19F and 18C, respectively, in PHiD-CV. 35 This was shown in previous studies to result in an enhanced anti-PRP response when a tetanus-conjugate Hib vaccine was co-administered with PHiD-CV. 35 In our study, we also observed a trend for a higher anti-PRP antibody GMC in the PHiD-CV group compared to the HAV control group, although this difference did not reach statistical significance.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 88%
“…35 This was shown in previous studies to result in an enhanced anti-PRP response when a tetanus-conjugate Hib vaccine was co-administered with PHiD-CV. 35 In our study, we also observed a trend for a higher anti-PRP antibody GMC in the PHiD-CV group compared to the HAV control group, although this difference did not reach statistical significance.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 88%
“…Finally, this study relied on measures of humoral immunity, which may less reliably predict disease risk than measures of cell-mediated immunity [36][37][38]. However, serologic evidence of immunity is the international standard by which vaccine immunogenicity is currently measured [37][38][39][40][41], and although seronegativity and disease susceptibility are not identical, loss of detectible antibody is associated with an increased risk of breakthrough disease [42].…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…The GMC of those vaccinated with PCV10 was 2.132 mg/mL (95% CI 1.925-2.362) compared to 1.176 mg/ mL (95% CI 0.973-1.423) in those vaccinated with PCV7, suggesting an enhancement of the anti-Hib response by the TT carrier used for serotype 18C in PCV10. 7 …”
Section: Carrier Specific Enhancement Of T-cell Helpmentioning
confidence: 99%